Zagadnienie Zginania i Wyboczenia Ram Złożonych z Prętów Kratowych o Zmiennych Sztywnościach Zginania - Krynicki, E.; Mazurkiewicz, Z. (Engineering Transactions, 1964)
Slope-deflection equations for the displacement method are derived thus enabling the solution of the buckling and bending problem of elastic structures (continuous beems and frames) composed of lattice elements with bending rigidities variable in usual ways.The equations obtained may be used to determine section forces and critical loads for industrial hells, crane frames, rate cranes, masts, high tension towers, some bridge elements and many other structures.